We are All Amina Filali: Social Media, Civil Society, and Rape legislation reform in Morocco - Ouassini, Anwar (Women & criminal justice, 2021)
In 2012 Amina Filali, a 16-year-old girl from Larache, Morocco was kidnaped, raped, and forced to marry her rapist under Article 475 of the Moroccan penal code. The decision by the courts to impose this law on Amina Filali forced her into an abusive relationship with her ‘husband’ and eventual suicide through the consumption of rat poison. This case was one of the first mediatized criminal events in post-Arab Spring Morocco and produced a domestic and global movement to repeal Article 475 and protect victims of rape. The paper will examine the case of Amina Filali and how digital mediums can be useful in promoting legal changes.